2022
DOI: 10.1007/s11033-021-07043-z
|View full text |Cite
|
Sign up to set email alerts
|

Trigger of apoptosis in adenocarcinoma gastric cell line (AGS) by a complex of thiosemicarbazone and copper nanoparticles

Abstract: Seeking novel anticancer agents with minimal side effects against gastric cancer is vitally important.Copper, as an important trace element, takes roles in different physiologic pathways. Also, there is a higher demand for copper in cancer cells than normal ones. Copper complexes containing a therapeutic ligand could be promising candidates for gastric cancer chemotherapy. In this work, copper oxide nanoparticles were synthesized, functionalized with glutamic acid (CuO@Glu) and conjugated with thiosemicarbazon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[72][73][74] Several copper bis(thiosemicarbazone) conjugates have shown promising anticancer properties. [75][76][77][78] Cu 2+ (atsm) is one of these complexes that retains its bonded metal in a reductive intracellular environment. Palanimuthu and coworkers (2013) chose two variants, copper(gtsc) (7) and copper(gtsc•HCl) (8), for their powerful anticancer effects, which was comparable to that of the widely used chemotherapeutic agent adriamycin.…”
Section: Chelators and Ionophores In Copper Transportmentioning
confidence: 99%
“…[72][73][74] Several copper bis(thiosemicarbazone) conjugates have shown promising anticancer properties. [75][76][77][78] Cu 2+ (atsm) is one of these complexes that retains its bonded metal in a reductive intracellular environment. Palanimuthu and coworkers (2013) chose two variants, copper(gtsc) (7) and copper(gtsc•HCl) (8), for their powerful anticancer effects, which was comparable to that of the widely used chemotherapeutic agent adriamycin.…”
Section: Chelators and Ionophores In Copper Transportmentioning
confidence: 99%
“…A team led by Badrooh developed a spherical-shaped complex of TSC and CuNPs whose size was varying from 10 to 60 nm that can trigger the apoptosis of Adenocarcinoma gastric. The study proved that the synthesized complex proficiently depleted the augmentation of AGS cells with significantly reduced IC 50 reading (203 μg/mL) than HEK293 (IC 50 = 435 μg/mL) ( Badrooh et al, 2022 ).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, researchers observed that Cu levels were higher in the serum and tissues than those in healthy control groups when cancer patients were in advanced stages [ 24 ]. Likewise, previous studies implied a higher demand for Cu in cancer cells, which would be a breakthrough point to slow cancer progression [ 25 ]. Cu is considered a promising anticancer targeting agent [ 26 ].…”
Section: Discussionmentioning
confidence: 99%